1996
DOI: 10.1093/carcin/17.9.2077
|View full text |Cite
|
Sign up to set email alerts
|

Cx32 gene mutation in a chemically induced rat liver tumour

Abstract: Cx32 is a major gap junction protein of the liver and is often aberrantly expressed in liver tumours. We have studied mutation of the Cx32 gene during chemically induced hepatocarcinogenesis. DNA from 12 rat liver tumours induced by diethylnitrosamine or N-ethyl-N-hydroxyethylnitrosamine (EHEN) was analysed by the PCR/SSCP method. One tumour induced by EHEN harboured a G--> A transition mutation at codon 220, substituting His for Arg. When the mutant DNA was transfected into HeLa cells, which are deficient in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 25 publications
3
28
0
Order By: Relevance
“…16 It is well established that promoter methylation can result in decreased expression of tumor suppressor genes such as p16, p15, RB, VHL, hMLH-1, APC and BRCA1 genes, and contributing to increased tumorigenicity in a variety of human cancers. 11 Previous studies has shown that cellspecific transcription of Cx32 and Cx43 in hepatic cells is controlled by promoter methylation, 17 suggesting that the methylation within promoters might involve in transcriptional inhibition of connexin genes in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…16 It is well established that promoter methylation can result in decreased expression of tumor suppressor genes such as p16, p15, RB, VHL, hMLH-1, APC and BRCA1 genes, and contributing to increased tumorigenicity in a variety of human cancers. 11 Previous studies has shown that cellspecific transcription of Cx32 and Cx43 in hepatic cells is controlled by promoter methylation, 17 suggesting that the methylation within promoters might involve in transcriptional inhibition of connexin genes in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, up to now, mutations of connexins have rarely been found in cancer cells. One mutation at codon 220 of Cx32 was detected in one out of 12 rat liver tumors studied (Omori et al, 1996b). Three out of 25 rat hemangiosarcomas showed a mutation at codon 319 of Cx37 (Saito et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several missense mutations of Cx32 in the 3M domain (although not at positions of polar residues) have also been found in CMTX patients and their inhibitory eect on GJIC has been con®rmed experimentally (Bruzzone et al, 1994;Omori et al, 1996;Deschenes et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The connexin (Cx) genes have been classi®ed as tumor suppressors (Yamasaki and Naus, 1996). Several mechanisms have been shown to be responsible for abnormal GJIC in tumors, including down-regulation of Cx protein expression (Lee et al, 1991) and aberrant intracytoplasmic localization of connexins Neveu et al, 1994); in a few instances mis-sense mutations in the coding area of a Cx gene have been found in tumors (Saito et al, 1997), some of which aected Cx function (Omori et al, 1996). The notion that connexins act as tumor suppressors has been strengthened by transfection experiments.…”
Section: Introductionmentioning
confidence: 99%